2021
DOI: 10.1002/pa.2692
|View full text |Cite
|
Sign up to set email alerts
|

Do earnings management practices define the readability of the financial reports in India?

Abstract: Using a sample of the listed firms over the period 2007-2019, we examine the impact of financial statement readability on the earnings management in a large emerging economy, India. Besides, we test for the readability of financially distressed and financially constrained firms. We use the fog index to measure the readability of the Management Discussion and Analysis (MDA) section of the annual report, and earnings management is measured using the Jones model. Our results indicate that the firms practicing ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…Bradley et al (2021) findings demonstrated a strong positive relationship between unverifiable net assets and reading difficulties for earnings management. Businesses used profitable management techniques to generate less readable financial reporting (Arora & Chauhan, 2021). According to Pakawaru et al (2021) study, management conceals unethical behaviour from stakeholders by using CSR disclosure.…”
Section: Discussion On Earnings Management Disclosurementioning
confidence: 99%
See 4 more Smart Citations
“…Bradley et al (2021) findings demonstrated a strong positive relationship between unverifiable net assets and reading difficulties for earnings management. Businesses used profitable management techniques to generate less readable financial reporting (Arora & Chauhan, 2021). According to Pakawaru et al (2021) study, management conceals unethical behaviour from stakeholders by using CSR disclosure.…”
Section: Discussion On Earnings Management Disclosurementioning
confidence: 99%
“…journal.ump.edu.my/jgi ◄ Boskou et al, 2020, Campa, 2020, El-Din et al, 2021 Strong positive relationship between difficulties and earnings management. Bradley et al, 2021, Arora andChauhan, 2021 CSR Management conceals unethical behaviour by using CSR disclosure. Pakawaru et al, 2021, Mahmood et al, 2020 No relationship between culture and earnings management.…”
Section: Discussion On Earnings Management Disclosurementioning
confidence: 99%
See 3 more Smart Citations